Wound healing mechanism of antimicrobial peptide cathelicidin-DM - Wang, Guixi; Chen, Zhizhi; Tian, Pan; Han, Qinqin; Zhang, Jinyang; Zhang, A-Mei; Song, Yuzhu (Frontiers in Bioengineering and Biotechnology, 2022)
Background and Purpose: Chronic wound infections and the development of antibiotic resistance are serious clinical problems that affect millions of people worldwide. Cathelicidin-DM, an antimicrobial peptide from Duttaphrynus melanostictus, has powerful antimicrobial activity and wound healing efficacy. So, it could be a potential candidate to address this problem. In this paper, we investigate the wound healing mechanism of cathelicidin-DM to establish a basis for preclinical studies of the drug. Experimental Approach: The effects of cathelicidin-DM on cell proliferation and migration, cytokines, and mitogen-activated protein kinase (MAPK) signaling pathways were examined. Then mice whole skin wound model was constructed to evaluate the wound healing activity of cathelicidin-DM, and further histological changes in the wounds were assessed by hematoxylin-eosin staining (H&E) and immunohistochemical assays. Key Results: Cathelicidin-DM promotes the proliferation of HaCaT, HSF, and HUVEC cells in a concentration-dependent manner and the migration of HSF, HUVEC, and RAW.264.7 cells. Moreover，cathelicidin-DM can involve in wound healing through activation of the MAPK signaling pathway by upregulating phosphorylation of ERK, JNK, and P38. However, cathelicidin-DM didn’t affect the secretion of IL-6 and TNF-α. At the animal level, cathelicidin-DM accelerated skin wound healing and early debridement in mice as well as promoted re-epithelialization and granulation tissue formation, α-SMA expression, and collagen I deposition in mice. Conclusion and Implications: Our data suggest that cathelicidin-DM can be engaged in the healing of infected and non-infected wounds through multiple pathways, providing a new strategy for the treatment of infected chronic wounds.